ANALYSIS OF THE IMPACT OF BLASTING TUNNEL # 4 ON THE JAKARTA-BANDUNG FAST TRAIN PROJECT ON RESIDENCE - Pratama, Rengga
PT. SINOHYDRO together with PT. Kereta Cepat Indonesia Cina (KCIC) is currently working on the Jakarta-Bandung fast train tunnel construction project. One of the tunnels currently being worked on is tunnel # 4 in Sukatani District, Purwakarta Regency. Tunnel # 4 is planned to use mechanical excavation for soft materials in the form of silty clay and silty sand and blasting methods for hard materials in the form of andesite rock. This research was conducted with the aim of predicting the amount of PVS, PPA, and PPD as a result of the blasting in the vicinity of tunnel # 4 KCIC. Data was collected directly in the field using the Instantel "Minimate Plus" tool. Data processing was processed using the Blastware application and Microsoft Excel. The impact of blasting in tunnel # 4 does not exceed the NAB (Threshold Value) of vibration for Class 1 SNI 7571: 2010, namely PVS = 3 mm / all frequency = 5-20 Hz. The impact of the blasting did not increase the value of the fracture in the community houses around tunnel # 4. From the results of data processing, the predicted values of Peak Vector Sum (PVS), Peak Particle Acceleration (PPA), Peak Particle Displacement (PPD) were obtained. With the equation PVS = 747.6 SD -1.48, PPA = 79.89 SD -1.64, PPD = 5.94 SD -1.6